Effects of Short-Term Streptozotocin-Induced Diabetes and Vitamin C on Platelet Non-Enzymatic Glycation - YARAT, AYŞEN; BATIREL, SAİME (KARGER, 2009)
Diabetes mellitus is one of the most prevalent metabolic syndromes worldwide. Glycation, a chemical modification of proteins with reducing sugars, indicates a possible explanation for the association between hyperglycemia and the wide variety of tissue pathologies. Non-enzymatic glycation (NEG) of platelet proteins is one of the key mechanisms in the pathogenesis of diabetic complications and may be significant in diabetic atherothrombosis. The aim of this study was to investigate the effects of streptozotocin (STZ)-induced short-term experimental diabetes on the glycation of platelets and to find out if vitamin C affected this glycation. A total of 40 male Wistar albino rats, 200-250 g, were randomly divided into 4 groups (2 diabetic and 2 control groups). The diabetic groups were made diabetic by intraperitoneal injection of STZ (65 mg/kg, citrate buffer pH 4.5). By daily intraperitoneal injection, 80 mg/kg vitamin C (Roche, Turkey) was administered until the end of the experiment. Blood glucose levels of the diabetic groups were significantly higher than those at day 0 and also higher than those of the non-diabetic control groups. The changes in total protein, NEG and vitamin C levels were not statistically significant. Although the differences among the groups were not statistically significant, vitamin C administration increased NEG levels in the diabetic group. The results of this study demonstrate that 8 days of STZ-induced short-term diabetes did not cause a significant increase in NEG of platelets. However, the effect of vitamin C on platelet NEG needs to be further investigated. Copyright (C) 2011 S. Karger AG, Basel
Keywords: Diabetes; Streptozotocin; Vitamin C; Platelet; Glycation